Sustainable construction materials : copper slag - Dhir, Ravindra K.; Brito, Jorge de; Mangabhai, Raman; Lye, Chao Qun (Woodhead Publishing series in civil and structural engineering., 2017)
Sustainable Construction Materials: Copper Slag, as part of a series of five, the book aims to promote the use of sustainable construction materials. It is different to the norm and its uniqueness lies in developing a data matrix sourced from 400 publications, contributed by 712 authors from 337 institutions in 40 countries from 1964 to 2015, on the subject of copper slag as a construction material, and systematically, analysisng, evaluating and modelling this information for use in cement, concrete, geotechnics and road pavement applications. Related environmental issues, case studies and standards are also discussed. The work establishes what is already known and can be used. It would also help to avoid repetitive research and save valuable resources, which can instead be directed towards new research to progress the use of sustainable construction materials. The book is structured in an incisive and easy to digest manner. As an excellent reference source, the book is particularly suited for researchers, academics, design engineers, specifiers, contractors, developers and certifying and regulatory authorities, seeking to promote sustainability within the construction sector.